2002
DOI: 10.1046/j.1525-1497.2002.10309.x
|View full text |Cite
|
Sign up to set email alerts
|

Managed care, primary care, and the patient-practitioner relationship

Abstract: Managed health plans that loosen restrictions on provider choice, relax gatekeeping arrangements, or promote access to and continuity with PCPs, are likely to experience higher patient satisfaction with their primary care practitioner relationships. Lack of health insurance impedes the development of patients' relationships with their primary care practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…Schmittdiel et al (23) found that patients in a large group-model health maintenance organization with the opportunity to select their own PCP were 16 -20% more likely to be satisfied with their care. Forrest et al (29) found that patients who believed they had a greater choice of PCPs tended to rate the patient-PCP relationship more favorably. Although most of these studies focused on the choice of PCP or hospital stay, our study was, to our knowledge, the first to suggest an association between satisfaction with elective surgery and opportunity to choose the hospital for such a procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Schmittdiel et al (23) found that patients in a large group-model health maintenance organization with the opportunity to select their own PCP were 16 -20% more likely to be satisfied with their care. Forrest et al (29) found that patients who believed they had a greater choice of PCPs tended to rate the patient-PCP relationship more favorably. Although most of these studies focused on the choice of PCP or hospital stay, our study was, to our knowledge, the first to suggest an association between satisfaction with elective surgery and opportunity to choose the hospital for such a procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[16] One study found that having more managed care patients in a physician's panel is associated with lower patient satisfaction with the provider. [17] With the quantity and quality of physician-patient communication being reported as a possible predictor of medical liability claims, [18][19][20] it is possible that physicians with higher managed care involvement are more vulnerable to malpractice claims.…”
Section: Discussionmentioning
confidence: 99%
“…They reflect managed care plan restrictiveness and have been shown to adversely affect the PPR for the general population. 9 We included a payer variable to measure individuals' insurance coverage. It was coded as Medicare, employerbased private insurance, individually purchased private insurance, Medicaid, or uninsured.…”
Section: Methodsmentioning
confidence: 99%
“…9 With this study, we aimed to determine whether patients' perceptions of their PPR vary by vulnerability status (i.e., the likelihood of poor future health because of greater-than-average health care needs) and assess the extent to which gatekeeping arrangements and primary care performance moderate potential disparities.…”
mentioning
confidence: 99%